2019
DOI: 10.7150/jca.26444
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering Microenvironment of NSCLC based on CD8+ TIL Density and PD-1/PD-L1 Expression

Abstract: Purpose: To determine whether distinct tissue immune microenvironments differentially impact on clinical outcome in non-small cell lung cancer (NSCLC), an extended analysis of PD-1/PD-L1 and Tumor Infiltrating Lymphocytes (TILs) was performed.Materials and Methods: 1016 NSCLC mRNA-sequence samples from The Genome Data Analysis Center (TCGA) and 275 NSCLC mRNA-microarray samples from Gene Expression Omnibus (GEO) were included as testing cohort and validation cohort respectively. Enrichment scores of CD8+ T cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 50 publications
(50 reference statements)
1
26
1
Order By: Relevance
“…Others showed that the extent of immunological infiltration in tumor tissue and the expression of immune checkpoints proved to be a reliable marker for response to anti-PD-1 immunotherapy and long-term survival NSCLC [38], and other malignancies, like breast cancer [39], melanoma [40], colorectal carcinoma [41], and prostatic cancer [42] as well. Another group indicated on NSCLC TMA samples that a high number of stromal CD4 + and epithelial and stromal CD8 + cells were independent positive prognostic markers, and CD8 + tumor-infiltrating lymphocytes (TILs) can stratify immunotherapy-treated patients of different clinical outcome [43]. Furthermore, a low level of CD8 + lymphocyte infiltration in tumor stroma was positively correlated with an augmented incidence of angiolymphatic tumor invasion [38].…”
Section: Discussionmentioning
confidence: 99%
“…Others showed that the extent of immunological infiltration in tumor tissue and the expression of immune checkpoints proved to be a reliable marker for response to anti-PD-1 immunotherapy and long-term survival NSCLC [38], and other malignancies, like breast cancer [39], melanoma [40], colorectal carcinoma [41], and prostatic cancer [42] as well. Another group indicated on NSCLC TMA samples that a high number of stromal CD4 + and epithelial and stromal CD8 + cells were independent positive prognostic markers, and CD8 + tumor-infiltrating lymphocytes (TILs) can stratify immunotherapy-treated patients of different clinical outcome [43]. Furthermore, a low level of CD8 + lymphocyte infiltration in tumor stroma was positively correlated with an augmented incidence of angiolymphatic tumor invasion [38].…”
Section: Discussionmentioning
confidence: 99%
“…The status of CD8 + TILs has been generally reported to be correlated with better prognosis ( 33 35 ). Our results did demonstrate that CD8 + TILs could play pivotal roles in possible biological behavior of PHEOs and its abundance could also represent relatively benign tumors as reported in other human malignancies ( 33 35 ). However, it awaits further investigations for clarification.…”
Section: Discussionmentioning
confidence: 99%
“…The critical importance of CD8+T-cells was also shown by Lin et al involving 1016 NSCLC mRNA-sequence samples from The Genome Data Analysis Center (TCGA) and 275 NSCLC mRNA-microarray samples from Gene Expression Omnibus (GEO) as testing and validation cohort, respectively. Lin showed that CD8+T-cell infiltration was associated with improved survival [18]. A separate study by Fumet et al looking again at the mRNA sequencing in 1016 NSCLC TCGA samples and 85 samples of NSCLC patients treated with anti-PD-1 for comparison with OS and PFS, respectively, found that CD8 was associated with both a good PFS and OS, while PD-L1 (RNA) was associated with a poor OS in ICI-untreated patients and with a good PFS and OS in patients treated with anti-PD-1 therapy [19].…”
Section: Cd8 a Critical Til Subsetmentioning
confidence: 99%